Fear of Missing Out (FOMO) among climbers: Questioning the mountain climbing tourism industry in Indonesia in the context of contemporary change - Ilman Nafi’a (Priviet Social Sciences Journal, 2026)
Mountain climbing in Indonesia has transformed significantly from a specialized exploration activity into a popular mass tourism industry, mainly driven by the influence of social media. This growth has made mountain climbing tourism one of the country's foreign exchange contributors, attracting millions of domestic and foreign climbers annually. However, this popularity has given rise to the psychological phenomenon of Fear of Missing Out (FOMO), a social anxiety that drives individuals to follow climbing trends without adequate understanding or preparation. Using a literature review method based on credible journals, news sites, and social media platforms, this paper aims to analyze the phenomenon of the mountain climbing tourism industry in the contemporary era in relation to the emergence of FOMO as a driver of social change. This study specifically examines how FOMO has caused a shift in the meaning and motivation of climbing, from an adventure activity to a lifestyle based on trends. Furthermore, it analyzes how this change in motivation will have a reciprocal impact on the sustainability of the mountain climbing tourism industry in the future. Ultimately, this study identifies the contradictions that arise when tourism drives social change among climbers in the region.